The Effect of Commodity Price on Indonesia Rupiah Exchange Rate and Dow Jones Index on Indonesia Stock Exchange - Siti Hernita Oktavia; Anis Rachma Utary; Felisitas Defung (Universitas Warmadewa, 2018)
Capital market is one of today's economic instruments that has developed very rapidly. One way to measure the performance of capital market is through stock index. There are many affecting factors to the stock index, such as domestic interest rates, foreign exchange rates, international economic conditions, the country's economic cycle, inflation rates, tax regulations, the amount of money in circulation (M. Samsul, 2008). The purpose of this study is to analyze the effect of Oil Prices, World Gold Prices, Exchange Rate of Indonesian Rupiah, and Dow Jones on IHSG (Indonesia Stock Exchange). We used analytical method with multiple regression analysis performed with SPSS 24 to conduct the study. In advance to applying multiple regression analysis, we administered a classic assumption test. This is necessary to make the regression equation is BLUE (Best, Linear, Unbiased, Estimator). Results of data analysis showed that Gold Price and Indonesia Rupiah Exchange rate negatively affected the Indonesia Stock Exchange; the Oil Prices and Dow Jones index also had a positive effect on Indonesia Stock Exchange. The value of adjusted R square is 59.7%. This means that by 59.7% Indonesia Stock Exchange movement can be predicted from the movement of the independent variables.